Imitation Modeling of Production Processes in FlexSim Environment - E. V. Lapteva; Yu. S. Lekareva; S. S. Umansky (Вестник Российского экономического университета имени Г. В. Плеханова)
Modeling systems in present day life give opportunity to find optimum ways of enterprise functioning and changes in set parameters without interference in production processes or before starting the planned production. The article studies imitation modeling use in agricultural machine-building. Brief description of FlexSim software is provided. Functional features of the system of imitation modeling allow users to identify bottlenecks, analyze statistic data, plot diagrams, etc. Imitation models of production processes on assembly line for seed-loaders are described, obtained results are analyzed and bottlenecks of the production line are identified. The authors study possibilities of optimization, which can raise productivity, for example, cutting the number of operators and introducing coordinators. The present research shows the importance of modeling and analyzing production processes in virtual environment in order to plan changes in production. Apart from modeling production processes, FlexSim program can be used for analyzing material, finance, information, staff resources, which affects managerial decision-making and strategy of industrial enterprise development.